Evaluation of Planting Technologies in Winter Canola - M. A. Secchi; Y. Wright; C. Foster; M. J. Stamm; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
Winter canola (Brassica napusL.) stand establishment and winter survival are two of the most important limitations to canola production faced by farmers. We hypothesize that planting canola with a system that provides accurate in-row spacing will positively impact crop establishment, survivability, and reduce seed input costs. A planting system that provides a homogenous spatial and temporal distribution of canola plants will also positively affect yield. The objective of this study was to investigate the impact of three metering systems with different opener and seed delivery systems on stand establishment, spatial distribution, and yield at three seeding densities and under two potential yield levels within a field. To test this hypothesis, three on-farm research studies were evaluated in the south-central region of Kansas. Preliminary results indicate that in homogenous environments, new planting technologies have a positive impact on the spatial distribution of plants within a row.
Keywords: Brassica napus; stand establishment; canola distribution